Pengembangan Jobsheet Praktik Pekerjaan dasar Elektromekanik di Sekolah Menengah Kejuruan - Ronal Hasiholan Hrp; Mukhlidi Muskhir (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2020)
This research is motivated by the limited teaching materials that lead students to understand more easily in the practical learning process. The practical subject of Electromechanical Basic Work is one of the subjects at SMKN 1 Tilatang Kamang in the Electrical Power Installation Engineering Department. One of the factors that support the smooth implementation of practicum is the availability of a jobsheet as a guide in practice In this study, a jobsheet was developed to obtain a valid and practical jobsheet to use for basic electromechanical work practice. Jobsheet development is carried out based on the 4D development research method, which includes defining, designing, developing and disseminating stages. The validity of the jobsheets is evaluated through media and material experts, while the practicality of the jobsheets is evaluated through users. The validity and practicality of the jobsheet were tested using a questionnaire. The results showed that the jobsheets developed for the subject of Basic Electromechanical Work were feasible to use. This can be seen from the results of practicality tests and validity tests that have been carried out. The results of the validity test of the three validators obtained an average score of 0.79 validity value in the valid category, while the practicality test results from the teacher obtained a score of 91.4 with the very practical category. From the results of this assessment, it can be interpreted that the job sheet media for Basic Electromechanical Work is suitable for use as a learning resource for class X students of Electrical Power Installation Engineering.